Environmentally friendly synthesis of Wells-Dawson heteropolyacids. Active acid sites investigation through TPSR of isopropanol - Matkovic, Silvana Raquel (2008)
Fosfo-tungstic and fosfo-molybdic Wells-Dawson heteropolyacids, H6P2W18O62·xH2O and H6P2Mo18O62·xH2O respectively, were synthesized through ion-exchange. This novel method possesses a higher yield (∼90%) than the conventional organic route (∼70%). Wells-Dawson heteropolyacids are obtained when the corresponding ammonium salt [(NH4)6P2W18O62·13H2O or (NH4)6P2Mo18O62·12H2O] is kept in contact with an acid resin [about (1:0.8) salt:resin weight ratio] up to 3 days. The use of an organic media instead of an aqueous media greatly favors the completeness of the exchange. Temperature programmed surface reaction of chemisorbed isopropoxy species towards propylene allows determined the number of active acid surface/bulk sites and the activation energy of the surface reaction. This parameter provided evidences of the influence of the central phosphorous atom and oxide supports on the acid strength of the active sites. © 2008 Elsevier B.V. All rights reserved.